Zukunftsfeld Bildungs- und Berufsberatung IV Schwierige Zeiten - Positionierungen und Perspektiven - Hammerer, Marika; Kanelutti-Chilas, Erika; Krötzl, Gerhard; Melter, Ingeborg (Zukunftsfeld Bildungs- und Berufsberatung, 2017)
The transcript comprises different views and options for action within educational and vocational guidance and counselling in the face of social, economic and labour-market changes. Professional theory and practical occupational approaches constitute the emphasis of this paper. Furthermore, the authors address the role of educational and vocational guidance and counselling as well as the execution and interpretation of the same by the counsellors - both individual and as an occupational group. The contributions are divided into four central issues: What determines the daily work of the counsellors and how do they handle it? Which challenges does migration entail? How can the professional theory of educational and vocational guidance and counseling be differentiated and developed further? How can potentials and resources be identified and extended?